The Relationship of Dietary Pattern and Dyslipidemia Incidence Using 12 Year Follow-up Cohort Data (P18-077-19) - Lee, Hae-Jeung (Curr Dev Nutr, 2019)
OBJECTIVES: Dietary pattern has more influence than single food or nutrient on development of chronic diseases. This study aimed to examine the relationship between dietary patterns and dyslipidemia risk using 12-year follow-up cohort data. METHODS: This study population consisted of middle-aged adults (40–69 years at baseline, n = 10,030) of Korean Genome and Epidemiology Study (KoGES) cohort that was initiated in 2001. The follow-up examinations are conducted biennially. Dietary intake was assessed using validated semi-quantitative food frequency questionnaire. Dietary patterns were identified by principal component analysis based on frequency (per week) of 36 food groups. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using the multivariate Cox proportional hazards regression model. RESULTS: Three dietary patterns were identified, namely “whole grain and soybean products” pattern, “low carbohydrate and variety” pattern, and “bread and noodle” pattern. During the 12-year follow-up period, 1429 and 1420 subjects were newly diagnosed with hypertriglyceridemia and hypercholesterolemia respectively. High intake of a “whole grain and soybean products” pattern (rich in whole grain, soybeans, tofu, soybean paste etc.) decreased hypertriglyceridemia incidence (HR: 0.79, 95% CI: 0.66–0.95, p for trend = 0.008) and showed a tendency to reduce hypercholesterolemial risk. CONCLUSIONS: A high intake of whole grain and soybean products may have beneficial effect on dyslipidemia. FUNDING SOURCES: Korea Food Research Institute.